Calcium-dependent mechanisms involved in the modulation of tyrosine hydroxylase by endothelins in the olfactory bulb of normotensive rats - Nabhen, Sabrina Laura (2013)
Endothelins (ETs) are widely expressed in the olfactory bulb (OB) and other brain areas where they function as neuropeptides. In a previous study we reported that in the OB ET-1 and ET-3 participate in the long-term regulation of tyrosine hydroxylase (TH), the key enzyme in catecholamine biosynthesis. ETs stimulate TH activity by increasing total and phosphorylated enzyme levels as well as its mRNA. ET-1 response is mediated by a super high affinity ETA receptor coupled to adenylyl cyclase/protein kinase A and Ca2+/calmodulin-dependent protein kinase II (CaMK-II) activation whereas that of ET-3 through an atypical receptor coupled not only to these signaling pathways but also to phospholipase C (PLC)/protein kinase C pathway. Given the participation of PLC and CaMKII in the regulation of TH by ETs in the OB we sought to establish the contribution of calcium to ETs response. Present findings show that calcium released from ryanodine-sensitive channels and extracellular calcium were necessary to stimulate TH by ETs through CaMK-II. On the other hand, intracellular calcium released by the endoplasmic reticulum partially mediated ETs-evoked increase in TH mRNA but calcium influx and CaMK-II inhibition abolished the response. However calcium mechanisms were not involved in ETs-evoked increase in TH protein content. Present findings support that different sources of calcium contribute to the long-term modulation of TH activity and expression mediated by ETs in the rat OB.